Analisis Pemahaman Konsep Matematika Siswa Dalam Menyelesaikan Soal Materi Himpunan Berdasarkan Taksonomi Solo (Structure Of Observed Learning Outcomes) Pada Siswa Kelas Vii Smp Negeri 2 Baki - Wibawa, Hari, Masduki, S.Si, M.Si (2017)
The aim of this study is determine the students' mathematical understanding ability concept to solve material set problems by SOLO taxonomy. Informan of this study is VII F student at SMP Negeri 2 Baki. Data was collected by test as principal method and interviews method,. Auxilary methods such as observation method, and documentation method. This study uses qualitative methods which through 3 flows, data reduction, data presentation, and drawing conclusion. The result of this study shows students' mathematical understanding concept about set material based SOLO taxonomy: (1) The student who get scores above KKM has reached multi-structural level, student has been able to solve problems and incorporate some of the data relationship / information to solve problems. While on stage relational student has not been fully able to achieve because there are errors in the record member in the venn diagram but have been able to use some of the existing information and then apply the concepts into real problems. (2) While student who received score less than KKM only reached in uni-structural level. Students can only use a single information to resolve the problem. While at multistruktural level students have not been able to use some of the information that is discrete, and can create a relationship of such information, as well as on the relational level students have not been able to use some of the existing information and then apply the concepts into real problems.